Performance improvement of dye-sensitized solar cells by using natural chlorophyll and anthocyanin dyes - Miladina Rizka Aziza; Eka Maulana; Panca Mudjirahardjo; Jumiadi Jumiadi (Institute of Advanced Engineering and Science, 2023)
Natural dye-sensitized solar cells (DSSC) have gained so much attention in recent years due to its low-cost fabrication process, ease of fabrication, and environmentally friendly. In order to improve the DSSC performance, the absorbance spectral of dyes must reach the maximum visible spectrum values. The combination of two dyes with different absorbance spectra can be utilized to expand the absorbance spectral. Here, we demonstrated the combination of natural chlorophyll and anthocyanin dyes from cassava leaves and black sticky rice, respectively, to enhance the DSSC performance. Our findings provide insights for increasing the DSSC performance by varying the combination of natural dyes. The highest efficiency was obtained from Chlorophyll:Anthocyanin 3:1.